2006
DOI: 10.4103/0253-7613.24617
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory activity of leaf extracts ofKalanchoe crenataAndr

Abstract: The methylene chloride/methanol extract of K. crenata was ex-B.P. 812 Yaounde, Cameroon. tracted by using hexane, methylene chloride, ethyl acetate, and n-butanol. The antiin 2 Department of Animal Biology, flammatory profile of these extracts was investigated on the basis of paw edema induced Faculty of Science, University of by carrageenan. The n-butanol fraction (most potent) was further assessed through acute Dschang, BP 67 Dschang, inflammatory models induced by histamine, serotonin, and formalin. The chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 7 publications
1
25
0
3
Order By: Relevance
“…Previous studies reported that, plants are rich in alkaloids triterpenoids, flavanoids and saponins which showed present antiinflammatory activity (Haihua Shu et al, 2006;Theophile et al, 2006;Borgi et al, 2007) Preliminary phytochemical analysis performed in this study shows the present of triterpenoids, saponins, polyphenols, steroids, tannins and flavanoids in the seed extract of E. agallocha. The anti-inflammatory activity action of triterpenoids has been reported by many researchers (Vazquez et al, 1996;Suh et al, 1998';Huss et al, 2002).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies reported that, plants are rich in alkaloids triterpenoids, flavanoids and saponins which showed present antiinflammatory activity (Haihua Shu et al, 2006;Theophile et al, 2006;Borgi et al, 2007) Preliminary phytochemical analysis performed in this study shows the present of triterpenoids, saponins, polyphenols, steroids, tannins and flavanoids in the seed extract of E. agallocha. The anti-inflammatory activity action of triterpenoids has been reported by many researchers (Vazquez et al, 1996;Suh et al, 1998';Huss et al, 2002).…”
Section: Discussionsupporting
confidence: 52%
“…The anti-inflammatory activity action of triterpenoids has been reported by many researchers (Vazquez et al, 1996;Suh et al, 1998';Huss et al, 2002). Saponnins has also been reported to have anti-inflammatory activities by inhibition of the enzymes iNos, Cox-2 and lipoxygenase (Bermejo Benito et al, 1998;Li and Chu, 1999;Kim et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…Thirty minutes after the treatment of animals, they received subplantar injection of serotonin 1% (0.1 ml) or histamine 1% (0.1 ml). Oedema was determined 30 or 60 min after serotonin (Lanher et al, 1991;Dimo et al, 2006) or histamine injection (Dimo et al, 2006;Singh et al, 1996), respectively. Percentage of inhibition (Pi) is obtained by the previous formula.…”
Section: Serotonin and Histamine Induced Edemamentioning
confidence: 99%
“…In the present investigation, the antiinflammatory activity of different extracts of leaves of Bixa orellana were tested by (chemical) carrageenan induced rat paw edema method using Diclofenac sodium as standard [2,9,10] and in-vitro membrane stabilization of HRBCs [11,12].…”
Section: Assessment Of In-vivo and In-vitro Antiinflammatory Activitymentioning
confidence: 99%